1995
DOI: 10.1093/clinids/21.5.1322
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Haemophilus influenzae Types e and f as Significant Pathogens

Abstract: Non-type b encapsulated Haemophilus influenzae meningitis (two cases due to H. influenzae type e, two due to H. influenzae type f) was diagnosed in four children in a 6-month period at the University of Virginia. H. influenzae type b was the most common cause of bacterial meningitis in the United States before the introduction of an effective vaccine, whereas the other five encapsulated serotypes of H. influenzae rarely caused invasive disease. The clinical features of non-type b H. influenzae meningitis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 6 publications
2
46
1
3
Order By: Relevance
“…Similar to the present case, severe meningitis may occur in healthy individuals (7). The clinical features and therapy of Hie meningitis are the same as those for type b H. influenzae disease (11).…”
Section: H Influenzae Can Be Classified Into Non-typable and Typablesupporting
confidence: 77%
“…Similar to the present case, severe meningitis may occur in healthy individuals (7). The clinical features and therapy of Hie meningitis are the same as those for type b H. influenzae disease (11).…”
Section: H Influenzae Can Be Classified Into Non-typable and Typablesupporting
confidence: 77%
“…Nonencapsulated (nontypeable) strains are usually associated with noninvasive infections but can cause invasive disease, including neonatal sepsis (2)(3)(4)(5). Historically, Hib was the leading cause of bacterial meningitis in the United States and Canada (6). However, since the introduction of Hib capsular polysaccharide-protein conjugate vaccine in 1988, the incidence of invasive Hib disease has declined dramatically.…”
mentioning
confidence: 99%
“…Protection conEpidemiology of Haemophilus infl uenzae Serotype a, North American Arctic, [2000][2001][2002][2003][2004][2005] ferred by the Hib vaccine is specifi c to the type b polysaccharide capsule. It was suggested that reducing carriage of the vaccine type may open an ecologic niche, allowing increased colonization with non-type b strains of H. infl uenzae with the potential to become invasive (6,16). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ähnlich, wie es bei Bordetella pertussis, Streptococcus pneumoniae und Hepatitis-B-Viren beobachtet wird, wird jedoch seit Beginn der HibImpfära vermehrt über Infektionen mit anderen Hämophilus-Serotypen berichtet, in den USA etwa mit Typ e und f [74,75]. In Deutschland stieg die Zahl von invasiven Erkrankungen mit Hämophilusbakterien anderen Typs von 10 im Jahr 1998 auf 22 im Jahr 2002 [76].…”
Section: Hibunclassified